The Oxford handbook of international cultural heritage law - Francioni, Francesco; Vrdoljak, Ana Filipa (Oxford : Oxford University Press, 2020)
This handbook provides a cutting edge study of international cultural heritage law, taking stock of the recent developments, core concepts, and current challenges.
Introduction / Ana Filipa Vrdoljak, Francesco Francioni -- Grasping the Nettle of Illicit export, import, and transfer / Folarin Shyllon -- World Cultural Heritage / Francesco Francioni -- Landscape as Cultural Heritage / Amy Strecker -- Underwater Cultural Heritage / Patrick J. O'Keefe -- The Environment and Cultural Heritage / Ben Boer -- Safeguarding Intangible Cultural Heritage / Janet Blake -- Language as Cultural Heritage / Bruno de Witte -- Cultural Heritage and Human Rights / Yvonne Donders -- Indigenous Peoples and Cultural Heritage / Dalee Sambo Dorough, Siegfried Wiessner -- Cultural Heritage and Women / Joseph Powderly, Rafael Braga da Silva -- The Intellectual Cooperation Organisation, UNESCO and Culture Conventions: A Historical Overview / Ana Filipa Vrdoljak, Lynn Meskell -- Cultural Heritage and Intellectual Property / Mira Burri -- Cultural Heritage and International Investment Law / Valentina Vadi -- National Treasures at the Intersection between Cultural Heritage and international trade law / Tania Voon -- Custom and general principles of international cultural heritage law / Francesco Francioni -- Cultural Heritage and State Immunity / Riccardo Pavoni -- Cultural Heritage and State Succession / Andrzej Jakubowski -- Cultural Heritage and State Responsibility / Patrizia Vigni -- Remedies / Elisa Novic -- International dispute resolution mechanisms / Marc-André Renold -- The role of domestic courts / Kurt Siehr -- Cultural Heritage and International Humanitarian Law / Roger O'Keefe -- Alternative dispute settlement mechanisms / Alessandro Chechi -- International Cultural Heritage Law: Institutional aspects / Tullio Scovazzi -- The Participation of non-state actors in the implementation of cultural heritage law / Kristin Hausler -- Codes of Ethics / Manlio Frigo -- Africa / Folarin Shyllon -- Asia / Keun-Gwan Lee -- Oceania / Craig Forrest, Jennifer Corrin -- Central and South America / Lucas Lixinski -- Europe / Rachael Craufurd Smith -- Middle East and North Africa / Morag M. Kersel, Mounir Bouchenaki -- Intentional Destruction of Heritage / Federico Lenzerini -- North American Cultural Heritage Law / Derek Fincham -- International Criminal Law and the Protection of Cultural Heritage / Micaela Frulli -- The Responsibilities to Protect Cultural Heritage and Prevent Cultural Genocide / James A. R. Nafziger -- Cultural Heritage and Disasters / Giulio Bartolini -- Cultural Heritage, Transitional Justice, and Rule of Law / Ana Filipa Vrdoljak -- Theft and Illicit Excavation / Patty Gerstenblith.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 2, 2020).
Keywords: Cultural property -- Protection (International law); Law; Laws of specific jurisdictions & specific areas of law